In situ analysis of LKB1/STK11 mRNA expression in human normal tissues and tumours. - Rowan, A; Churchman, M; Jefferey, R; Hanby, A; Poulsom, R; Tomlinson, I (2000)
The LKB1/STK11 serine/threonine kinase is mutated in Peutz-Jeghers' syndrome and acts as a tumour suppressor. Using northern blotting and RT-PCR, LKB1 has been reported to be expressed widely in human adult tissues, although in Xenopus the expression of its homologue, XEEK1, is apparently restricted to early embryogenesis. In situ hybridization has been used to detect and localize LKB1 mRNA in a variety of adult and fetal tissues and tumours. The results show that LKB1 expression is widespread, but predominant in epithelia and in the seminiferous tubules of the testis. Expression is higher in fetal than in adult tissues. Expression also appears to be higher in many malignant tumours than in normal tissues or benign lesions, although some cancers have lost LKB1 expression, quite possibly as part of the process of tumourigenesis. These data are consistent with a widespread functional role for LKB1 in tissues of most types, and with a role for LKB1 in the pathogenesis of some sporadic cancers. LKB1 expression may primarily be related to the rate of cell replication.